Conspiracy belief regarding emerging viral infection among healthcare professionals (Journal of Preventive and Social Medicine, 2024)
Background: In the recent past, newly appeared emerging and re-emerging viruses causing unexpected illness and epidemics among humans, wildlife and livestock causing threat to the public health. During onset of any pandemic, there was always an embrace of conspiracy theory regarding the pandemic along with several misconceptions, misperception and stigma among the general population. The study aimed to assess the state of conspiracy belief regarding emerging viral infection among the healthcare professionals working in Combined Military Hospital (CMH) Dhaka. Methods: This cross-sectional study was conducted during July and September 2022 among conveniently selected 254 healthcare professionals working in CMH Dhaka. Data were collected through face-to-face interview using a pretested semi-structured questionnaire with validated and reliable tools. Results: Among the 254 respondents, 53.9% were male with a mean age (±SD) of 30.54 (6.36) years. More than twothird (72.8%) were graduate, married (62.6%), mostly Muslim (89.4%) and non-smoker (80.3%) with an average (±SD) monthly income of 83740.16 (57456.80). Highest (45.3%) of the respondents were permanently posted and only 33.5% attended any seminar/workshop/symposium in last six months. Job pattern (β=0.199, p